Investigation Of SRR Parameters On Monopole Antenna Performance - Ong , Teik Kean; Abd Aziz, Mohamad Zoinol Abidin; Othman, Mohd Azlishah; Suaidi, Mohamad Kadim; Mohamad @ Sulaiman, Hanissah; F, .Abd. Malek (Asian Research Publishing Network (ARPN), 2015)
This paper presents an investigation of split ring resonator (SRR) parameters on a coaxial-fed monopole antenna.The adding of SRR slot can create a notch in the result of coaxial-fed monopole antenna design. Thus, this paper aims to investigate the effect of changes to the outer ring radius and slit cut width of the SRR slot. All antenna designs and simulations involved are drawn and simulated in Computer Simulation Technology (CST) Studio Suite software in an open space environment to prevent any interference within simualtion range. The antenna design is printed on a FR4 epoxy board with dielectric constant, εr of 4.4, tangent loss, tan δ of 0.019, and thickness, h of 1.6mm. In the investigation, outer ring radius of SRR slot has been increased from 4mm to 10mm whereas the slit cut width of SRR slot has been increased from 1mm to 8mm. The result shows that the increment of outer ring radius can shift the notch and frequency band to lower frequency. In a contrary, the widening of slit cut width of SRR slot is able to shift the notch and frequency band back to higher frequency. These two characteristics can contribute to wideband or ultrawideband system to provide frequency tunable notch function.